2020
DOI: 10.1186/s12929-020-00660-z
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous AMPK-regulated angiotensin AT1R expression and SIRT1-mediated mitochondrial biogenesis at RVLM in hypertension programming of offspring to maternal high fructose exposure

Abstract: Background: Tissue oxidative stress, sympathetic activation and nutrient sensing signals are closely related to adult hypertension of fetal origin, although their interactions in hypertension programming remain unclear. Based on a maternal high-fructose diet (HFD) model of programmed hypertension, we tested the hypothesis that dysfunction of AMP-activated protein kinase (AMPK)-regulated angiotensin type 1 receptor (AT 1 R) expression and sirtuin1 (SIRT1)-dependent mitochondrial biogenesis contribute to tissue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 73 publications
0
28
0
Order By: Relevance
“…Moreover, PPARγ can activate AMPK signaling (43,44). Notably, metformin, an AMPK activator, has been reported to reverse the increase in AT1R detected in response to a high-fructose diet (45). AT1R antagonists can regulate the proliferation and migration of vascular smooth muscle cells through AMPK/mTOR (46), and blocking AT1R can effectively inhibit activation of the AMPK/p38 MAPK/MCPIP1/ER pathway in macrophages (47).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, PPARγ can activate AMPK signaling (43,44). Notably, metformin, an AMPK activator, has been reported to reverse the increase in AT1R detected in response to a high-fructose diet (45). AT1R antagonists can regulate the proliferation and migration of vascular smooth muscle cells through AMPK/mTOR (46), and blocking AT1R can effectively inhibit activation of the AMPK/p38 MAPK/MCPIP1/ER pathway in macrophages (47).…”
Section: Discussionmentioning
confidence: 99%
“…The animals were placed into a stereotaxic head holder (Kopf, Tujunga, CA, USA) on a thermostatically controlled heating pad. Bilateral microinjection of the viral vectors was carried out, as described previously [ 32 , 44 ]. In brief, a glass micropipette (external tip diameter: 50–80 µm), connected to a 0.5-µL Hamilton microsyringe, was positioned into RVLM.…”
Section: Methodsmentioning
confidence: 99%
“…More recently, we found that maternal fructose reduces circulating high‐density lipoprotein (HDL)‐cholesterol levels in offspring, suggesting that maternal fructose consumption induces metabolic disorder in offspring. Other research groups also reported the maternal fructose intake‐induced impaired phenotypes such as hypertension, insulin resistance, and obesity 20–23 . It appears that offspring born from dams who consumed excess fructose are prone to physiological dysfunctions.…”
Section: Introductionmentioning
confidence: 95%
“…Other research groups also reported the maternal fructose intake-induced impaired phenotypes such as hypertension, insulin resistance, and obesity. [20][21][22][23] It appears that offspring born from dams who consumed excess fructose are prone to physiological dysfunctions. However, previous studies have focused primarily on phenotypic analysis.…”
Section: Introductionmentioning
confidence: 99%